Bladder antimuscarinics and cognitive decline in elderly patients. Issue 1 (9th February 2017) - Moga, Daniela Claudia; Abner, Erin L.; Wu, Qishan; Jicha, Gregory A.
Abstract: Introduction: The evidence on the impact of bladder antimuscarinics initiation on cognitive function in older adults is inconsistent. Methods: A retrospective analysis of data from the National Alzheimer's Coordinating Center (NACC) on enrollees 65 years and older evaluated the association between antimuscarinic initiation and cognitive decline. We defined decline from baseline (yes/no) for cognitive assessments included in the NACC Uniform Data Set 2.0 battery. New users were matched on year of enrollment and time in the cohort to randomly selected nonusers. Analyses were conducted using inverse probability of treatment weights based on baseline propensity scores. Results: Our analyses included 698 new users and 7037 nonusers. The odds ratio (OR) and 95% confidence interval for cognitive decline in users as compared to nonusers was 1.4 (1.19–1.65) for Mini–Mental State Examination (MMSE), and 1.21 (1.03–1.42) for Clinical Dementia Rating; in addition, the odds of decline were 20% higher in users compared to nonusers for semantic memory/language and executive function. The effect estimate for MMSE was 1.94 (1.3–2.91) for those with mild cognitive impairment, 1.26 (0.99–1.62) in those with normal cognition, and 1.44 (1.04–1.99) in those with dementia at baseline. Discussion: Our results show that antimuscarinic initiation is associated with cognitive decline and raise questions about their use, especially in those with impaired cognition.